Stock prices in a speculative market: The Chinese split-share reform - Andrea Beltratti; Bernardo Bortolotti; Marianna Caccavaio (Fondazione Eni Enrico Mattei (FEEM), 2009)
In 2005-2006 China reformed its stock market by eliminating non-tradable shares. The regulator set general guidelines and then assigned responsibility for implementation to each company. We derive relations that should have been followed by the prices of stocks and exploit a company-level data set to compare the actual and the theoretical price reactions. We find evidence for abnormal returns both before the beginning of the reform and during the reform. Cross-sectionally, abnormal returns are associated mainly with turnover and compensation. This shows that in a speculative market, investors do not properly react to unambiguous corporate actions.
Keywords: G14; N25; 330; Speculation; Chinese Stock Market; Market segmentation; Event study; Market Efficiency